Kontrola sądu administracyjnego w zakresie ustalania stanu faktycznego sprawy przez organ administracji publicznej jako istotny element prawa do sądu: [Review by administrative courts of actions taken by governmental bodies in establishing the facts of the case as an essential element of the right to bring an action before a court] (Studia Prawnicze / The Legal Studies, 2014)
Zasada prawa do sądu jako podstawa funkcjonowania demokratycznego państwa prawnego, formy państwa wytyczonej za cel przez art. 2 Konstytucji RP z 1997 r., wyraża się w przyjętej w art. 45 ust. 1 ustawy zasadniczej formule, zgodnie z którą – „Każdy ma prawo do sprawiedliwego i jawnego rozpatrzenia sprawy bez nieuzasadnionej zwłoki przez właściwy, niezależny, bezstronny i niezawisły sąd”. Stosownie do art. 77 ust. 2 Konstytucji – „Ustawa nie może nikomu zamykać drogi sądowej dochodzenia naruszonych wolności lub praw”. Prawo do ochrony sądowej jest proklamowane ponadto w ratyfi kowanych przez Polskę: Konwencji o ochronie praw człowieka i podstawowych wolności z 1950 r. (art. 6) oraz Międzynarodowym Pakcie Praw Obywatelskich i Politycznych z 1966 r. (art. 14). Jest ono również przedmiotem Rekomendacji Nr (2004)20 Komitetu Ministrów Rady Europy w sprawie sądowej kontroli aktów administracyjnych. In order to ensure that the right to bring an action before a court, which in substantive terms is understood as safeguard of the effective protection of individuals’ rights, is exercised and that a fair judgment is entered, the administrative courts may review the correctness of actions taken by governmental bodies in establishing the facts of the case, subject to the principle of legality. For this reason, it is necessary for the administrative courts to provide reasons for their judgments so as to demonstrate that the review of an administrative instrument was comprehensive and took account of all the facts of the case. The reasons so provided may cause the complainant to believe that he has indeed been granted legal protection. Moreover, this may demonstrate that the administrative courts not only review compliance with the principle of legality, but primarily exercise judicial power conferred on them. Therefore, it is appropriate to state that the applicable Polish regulations on the  administrative courts safeguard the individual’s right to bring an action before a court both in formal and material sense.